Development of low-cost deformation-based micro surface texturing system for friction reduction - Song, Xu (2016)
Surface texturing as a means for enhancing tribological properties of mechanical components has been under intensive investigation over the last two decades. Many methods have been proposed to create surface texture of various patterns and geometries. However, among all these methods, deformation-based micro-surface texturing is least studied. It has many advantages over other methods that could lead to immediate industry application, including high productivity, high geometry fidelity and low cost. In the current work, a simple but effective incremental micro embossing system based on a commercially available press has been developed to create micro surface textures of various shapes and depths with accuracy up to 5 μm. The friction coefficients of the textured surfaces have been tested at different loadings and speeds with various lubricants to demonstrate their friction reduction capability. It has been observed that at high speed conditions, the friction reduction is achieved by the hydrodynamic lift. Interestingly, at the low speed conditions, the micro-surface texture is still capable of reducing the friction, thanks to its lubricant retention and debris entrapment capability. A micro surface textured mechanical face seal demonstrator has been built to further evaluate the micro surface texture created by incremental embossing method. A reduction of 20% in torque friction has been consistently achieved, which is on a par with that of the laser surface texturing method.